Integrated Biomass Assessment and Optimized Power Generation. Issue 3 (30th January 2015) - Dimitrova, Elena; Vinklers, Janis; Chokani, Ndaona; Abhari, Reza S.
Abstract: Although power generation from wood biomass is among the fastest growing sectors of renewable power production, applied research that links biomass stock availability and the optimization of the location of the power plants is lacking. In this work, an integrated approach to determine the most economically viable locations for wood‐fired biomass power plants is presented. Forest vegetation maps are generated from recently available multiband satellite images. Field measurements in coniferous and broadleaved forests are used to derive tree‐stocking densities to determine, from the vegetation maps, the quantity of available wood biomass. A multimodal transportation and transmission grid network model is then used to identify the optimum locations for the top ten portfolios of 5, 15, and 20 MW power plants. It is shown that 15 MW power plants have the lowest levelized cost of energy and are the least susceptible to volatility in the wood price. Abstract : Wood you? An integrated approach to determine the most economically viable locations for wood‐fired biomass power plants is presented. Forest vegetation maps are generated from recently available multiband satellite images. We show that in Lublin Voivodeship, Poland 15 MW power plants have the lowest levelized cost of energy and are the least susceptible to volatility in the wood price.